Construction of a PPIL@COF core–shell composite with enhanced catalytic activity for CO2 conversion. Issue 6 (10th March 2021) - Du, Yi-Ran; Ding, Guang-Rong; Wang, Yao-Feng; Xu, Bao-Hua; Zhang, Suo-Jiang
Abstract : The porous poly(ionic liquid)-covalent organic framework (PPIL@COF) hybrids with core–shell structure were synthesized through surface modification of amino-functionalized PPIL and the interfacial growth with triazine-based TPT-DHTP-COF. Abstract : Converting CO2 into high value-added chemicals is a promising approach for CO2 utilization. It is imperative to develop novel catalysts for both selective and high adsorption of CO2 and thereafter efficient chemical transformation. Herein, bromide-based porous poly(ionic liquid)s (PPILs) were covalently integrated with mesoporous covalent organic frameworks (COFs) to provide a kind of core–shell hybrid for the first time. The resultant PPIL@COF hybrids fabricated by anchoring a specific ratio of PPIL to COF have a bromide per unit mass value which corresponds to the requisite CO2 uptake capacity, thereby facilitating the storage of enough CO2 around the catalytic active sites. As a proof of concept, the cyclization of epoxides with CO2 to form cyclic carbonates was selected as the benchmark reaction, the reactivity of which was significantly improved in the presence of hydroxyl group decorated PPIL@COF A compared to that of individual PPIL and the hydroxyl-free PPIL@COF B counterpart. The hydroxyl groups at the interfacial layer, functioning as the hydrogen bond donors, cooperate with the bromides from the PPIL core to facilitate the rate-limiting step of the ring opening of the epoxides. These findings provide the basis of a novel design concept for achieving both efficient and stable catalysts in the CO2 transformation.